SISTEM INFORMASI PERPUSTAKAAN PADA SMP NEGERI 2 OKU BERBASIS CLIENT SERVER - Sri Tita Faulina; wisnumurti wisnumurti (LPPM UNIVERSITAS BINA INSAN, 2021)
The school library is the most important part of the infrastructure in schools, because the library is a room in which it has a collection of books and magazines that are arranged regularly which is used by the community for reading and the library is also divided into several categories, one of which is the school library. School libraries need library information systems, especially libraries at SMP Negeri 2 OKU. This SMP Negeri 2 Library Information System was built using a client server based Embarcadero XE2. This research method is using interview and observation method, where the interview method is conducted to collect data face-to-face directly at SMP Negeri 2 OKU, the observation method is carried out to determine the process of borrowing and returning books by each student. The expected result of the Library Information System is to produce information quickly, and on time so as to facilitate the processing of book data, member data, borrowing data, return data, and report data.